Downstream Signaling of Muscarinic M4 Receptors Is Regulated by Receptor Density and Cellular Environment - Madeleine Merz; Charlotte Playle; Monika Palchaudhuri; Oliver Hucke; Ulrike Gross; Daniel Ursu (Pharmacology Research & Perspectives)
ABSTRACT Multiple muscarinic M4 receptor modulators are currently advancing in clinical development for the treatment of positive symptoms in schizophrenia, including agonists and positive allosteric modulators. Considering the importance of comprehending M4 receptor pharmacology for these therapeutic applications, this study investigates M4 receptor signaling pathways upon activation by structurally diverse muscarinic agonists, exploring the role of receptor expression levels and cellular environment on downstream signaling. HEK‐293 cells and rat primary neurons expressing human M4 receptors were used to measure the kinetics of cAMP levels and compound effects on neuronal network activity. Receptor expression levels were controlled by a Tet‐On system and quantified using a radioactive binding assay. Our findings revealed that most agonists caused a concentration‐dependent reduction of cAMP levels (Gi/o) at low concentrations, while inducing an increase in cAMP at higher concentrations (Gs). A less prominent coupling via Gs was observed when receptor density in HEK‐293 cells was reduced. In the neuronal assay, most compounds showed consistent inhibition of neuronal activity. A distinct group of agonists displayed a specific profile, with no Gs coupling at high receptor density, partial activation at low receptor density, and low to no effects in the neuronal assay. This study provides a side‐by‐side comparison of the activity of structurally diverse M4 agonists and highlights compound‐specific activation of GPCR intracellular signaling pathways. The data offer new insights into M4 receptor pharmacology that may aid in the development of novel therapies for the treatment of psychiatric diseases.